2007
DOI: 10.1097/hjh.0b013e3280e126bf
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin-converting enzyme inhibitor and exercise training on exercise capacity and skeletal muscle

Abstract: We found that in growing SHR, chronic treatment with perindopril enhances untrained exercise capacity, while it does not affect acquired exercise capacity as a result of exercise training. We also found that perindopril promotes adaptive changes of skeletal muscle in response to exercise such as increases in capillary density and percentage of type I fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…The activation of renin-angiotensin system, particularly the increase in angiotensin II (ANG II), has been well established to play an important role in the pathogenesis and progression of various cardiovascular diseases (7,15). Moreover, angiotensin-converting enzyme inhibitors have been shown to improve exercise capacity in patients with cardiovascular disease and in spontaneously hypertensive rats (5,22,34). These results suggest that ANG II may directly impair skeletal muscle function and reduce exercise capacity.…”
mentioning
confidence: 70%
“…The activation of renin-angiotensin system, particularly the increase in angiotensin II (ANG II), has been well established to play an important role in the pathogenesis and progression of various cardiovascular diseases (7,15). Moreover, angiotensin-converting enzyme inhibitors have been shown to improve exercise capacity in patients with cardiovascular disease and in spontaneously hypertensive rats (5,22,34). These results suggest that ANG II may directly impair skeletal muscle function and reduce exercise capacity.…”
mentioning
confidence: 70%
“…Similarly, it was reported that the ACEIs combined with exercise improved in physical performance but there was no effect when used ACEIs alone in rodents [59][60][61]. However, Sumukadas et al showed that ACEIs did not enhance the effect of exercise training on physical function Total represents the total number of patients.…”
Section: Discussionmentioning
confidence: 91%
“…The authors observed that chronic treatment with perindopril increases the exercise capacity in untrained animals; however, this effect was not synergic to the exercise capacity acquired as a result of ET alone. On the other hand, treatment with perindopril associated to ET promotes adaptive alterations in the soleus muscle, such as increase of capillary density and percentage of type I fibers 31 . Although no alteration in the composition of types of fiber was observed in the trained SHR and SHR treated with perindopril groups when compared with the sedentary SHR group, the authors observed higher capillarization in these groups, which may be attributed to improvement in the exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Minami et al 31 showed the effects of ET associated or not to treatment with perindopril (angiotensin-converting enzyme inhibitor), on the capillarity and fiber types in the soleus muscle of SHR. The authors observed that chronic treatment with perindopril increases the exercise capacity in untrained animals; however, this effect was not synergic to the exercise capacity acquired as a result of ET alone.…”
Section: Discussionmentioning
confidence: 99%